2012
DOI: 10.1016/j.ygyno.2012.08.010
|View full text |Cite
|
Sign up to set email alerts
|

17β hydroxysteroid dehydrogenase type 12 (HSD17B12) is a marker of poor prognosis in ovarian carcinoma

Abstract: Objective 17β-hydroxysteroid dehydrogenase isoform 12 (HSD17B12) overexpression is associated with poor clinical outcome in invasive ductal carcinoma of the breast. Here, we evaluated HSD17B12 overexpression and its activity in ovarian carcinoma (OvCa) to determine its role in growth and progression of this tumor. Methods Immunohistochemical analysis of HSD17B12 expression was performed in 100 tissue samples of untreated OvCa and was correlated with clinicopathologic characteristics and patient outcome. In A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 24 publications
3
24
2
Order By: Relevance
“…Of the four enzymatic entities participating in LCFA synthesis, 17β-HSD12 has garnered attention regarding its role in cancer through studies yielding conflicting results. While some studies reported an association of 17β-HSD12 with more aggressive tumor progression and poor outcome [21][22][23], others found a suppressive role [25]. Using different breast cancer cells, we showed that silencing of 17β-HSD12 either increases or decreases cancer cell proliferation and migration depending on the cellular context.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Of the four enzymatic entities participating in LCFA synthesis, 17β-HSD12 has garnered attention regarding its role in cancer through studies yielding conflicting results. While some studies reported an association of 17β-HSD12 with more aggressive tumor progression and poor outcome [21][22][23], others found a suppressive role [25]. Using different breast cancer cells, we showed that silencing of 17β-HSD12 either increases or decreases cancer cell proliferation and migration depending on the cellular context.…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, in two earlier reports, silencing of 17β-HSD12 expression, the enzyme performing the first reduction step in LCFA elongation (Fig. 1a), in one breast cancer and one ovarian cell line led to decreased proliferation, which could be reverted by AA supplementation [21,22]. These and one additional study found a correlation between high 17β-HSD12 expression and poor prognosis for survival in patients with breast and ovarian tumors [23].…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…The HSD17B12 gene encodes human 17 beta-hydroxysteroid dehydrogenase type 12, an enzyme involved in lipid metabolism [ 25 ]. Previous studies revealed that HSD17B12 could be a prognosis marker for several human cancers [ 26 28 ]. A recent study by Nguyễn et al showed that SNPs in HSD17B12 were associated with low-risk NBs, and rs11037575 was the most significant SNP in the HSD17B12 gene [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the normal ovary HSD17B is detected in granulosa cells of developing follicles, but not in the surface epithelium. In contrast, epithelial OvCa is positive for HSD17B, and its expression in OvCa is associated with poor prognosis [40]. The clinical implications attributed to HSD17B12 overexpression in OvCa suggest that it could serve not only as biomarker but also as candidate for T-cell based immunotherapy [41].…”
Section: Tissue Biomarkersmentioning
confidence: 99%